DETERMINATION OF POLYPHENOL AND FLAVONOID CONTENT AND ANTIOXIDANT ACTIVITY OF ETHANOLIC, CHLOROFORM AND ETHYL ACETATE EXTRACT OF THE PLANT SPECIES Thymus serpyllum L. - Aksić, Marija; Dekić, Biljana; Janićević, Suzana (Bulletin of Natural Sciences Research, 2023)
This research aimed to examine the phytochemical composition, content of polyphenols and flavonoids, and antioxidant capacity of ethanolic, ethyl acetate, and chloroform extract of the plant species Thymus serpyllum L. The extracts were tested for the presence of alkaloids, tannins, saponins, phenolic compounds, flavonoids, steroids, terpenoids, cardiotonic glycosides, and coumarins. The total content of polyphenols was determined spectrophotometrically with the Folin-Ciocalteu reagent, according to Singleton's method, while the total content of flavonoids was determined using the method with aluminum chloride. The highest contents of polyphenols and flavonoids were determined in ethanolic extracts, where the measured values ranged from 111.00 ± 0.26 to 288.00 ± 0.23 mg GAE/g of dry extract for polyphenols, and 65.80 ± 0.19 to 198.22 ± 0.34 mg RE/g dry extract for flavonoids. The antioxidant activity was determined by the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. The tested extracts show a good effect on DPPH radical inhibition, with the IC50 values ranging from 35.15 ± 0.33 to 398.27 ± 0.24 μg/ml, and the greatest ability of ethanolic extract to neutralize the DPPH radical. Qualitative phytochemical analysis of the extracts showed a wide spectrum of phytochemicals, where ethanol, as the most polar solvent, extracts almost all tested phytochemicals.
Keywords: Thymus serpyllum; Extracts; Polyphenols; Flavonoids; Phytochemicals; Antioxidant activity